Nilai-Nilai Akhlak dalam Kitab Bidāyah al-Hidāyah Perspektif Teori Pengembangan Kepribadian - Muhlishotin, Muhlishotin; Muhid, Abdul; Fuad, Ahmad Zakki (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2024)
This study aims to find out how the moral values in the book of Bidāyah al-Hidāyah discussed through perspective of personality development theory which includes four personality developments: religious education, habituation to discipline, habituation to ethics and noble character, and habituation to independence. This type of research includes library research with secondary data sources. As for the data collection technique, the study of documentation from the study of the main sources, namely the book of Bidāyah al-Hidāyah and relevant research literature. The data obtained were then be analyzed using content analysis and found as the results of this research, namely the indicative that the Bidāyah al-Hidāyah contains three moral values. The first moral value is that students in seeking knowledge must always remember Allah. Secondly, an educator must be responsible and authoritative. And thirdly, students must have good character, morals, and humility, especially towards kyai and/or ustadz.